Selenoprotein K Is Essential for the Migration and Phagocytosis of Immature Dendritic Cells - Huan Xia; Yongmei Wang; Jie Dai; Xin Zhang; Jun Zhou; Zhu Zeng; Yi Jia (MDPI AG, 2022)
Selenoprotein K (SELENOK) is an endoplasmic reticulum stress (ERS)-regulated protein required for the calcium (Ca2+) flux-mediated migration of T cells and neutrophils, and the migration and phagocytosis of macrophages and microglia. However, the effect of SELENOK on the regulation of the immune function of dendritic cells (DCs), including immature DCs (imDCs) and mature DCs (mDCs), is still unclear. In this study, imDCs prepared from SELENOK knockout mice were used to evaluate the effect of SELENOK on the migration and phagocytosis of imDCs. The results showed that ERS-induced downregulation of imDCs phenotypic markers led to a reduction in Ras homolog gene family member A (RhoA)-dependent migration and enhanced Ca2+/CD205-mediated phagocytosis. SELENOK deficiency-induced upregulation of selenoprotein S (SELENOS) attenuated ERS levels in imDCs. An increase in Ca2+ levels resulted in increased migration and decreased phagocytosis with or without ERS conditions. The migration was RhoA-dependent, and Ca2+ or CD205 was associated with regulating phagocytosis in imDCs. Our study found that SELENOK is required for imDC migration and phagocytosis.